2021
DOI: 10.3280/ecag3-2020oa11040
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic drivers in productive rural activities and their impact on the eating habits, lifestyle and nutritional status of people living in a rural area: The Majella National Park as a case study

Abstract: This paper analyses the relationship between food system dynamics with consumer behaviors, in population within a protected mountain area in Italy. In order to obtain socioeconomic and nutritional data, a combination of qualitative and quantitative research was employed to group farmers, local authorities, and inhabitants. Our research highlighted the close relationship between local food productive sector with consumption habits of local communities. The experience of the Majella National Park can be taken as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, several epidemiological studies have shown an inverse association between high intakes of plant protein (PP) and cardiometabolic risk and mortality [ 6 ]. Accordingly, unhealthy and unsustainable diets have been recognized as strongly contributing to the escalating burden of diet-related NCDs, aside from adversely impacting the local food systems and natural environment [ 7 , 8 ]. Population reference intakes for total protein (TP) are age specific and apply to mixed dietary protein from both animal and plant sources [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several epidemiological studies have shown an inverse association between high intakes of plant protein (PP) and cardiometabolic risk and mortality [ 6 ]. Accordingly, unhealthy and unsustainable diets have been recognized as strongly contributing to the escalating burden of diet-related NCDs, aside from adversely impacting the local food systems and natural environment [ 7 , 8 ]. Population reference intakes for total protein (TP) are age specific and apply to mixed dietary protein from both animal and plant sources [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%